The motor subsystem as a predictor of success in young football talents: A person-oriented study - Zibung, M.; Zuber, C.; Conzelmann, A. (PLOS ONE, 2016)
Motor tests play a key role in talent selection in football. However, individual motor tests only focus on specific areas of a player`s complex performance. To evaluate his or her overall performance during a game, the current study takes a holistic perspective and uses a person-oriented approach. In this approach, several factors are viewed together as a system, whose state is analysed longitudinally. Based on this idea, six motor tests were aggregated to form the Motor Function subsystem. 104 young, top-level, male football talents were tested three times (2011, 2012, 2013; Mage, t2011 = 12.26, SD = 0.29), and their overall level of performance was determined one year later (2014). The data were analysed using the LICUR method, a pattern-analytical procedure for person-oriented approaches. At all three measuring points, four patterns could be identified, which remained stable over time. One of the patterns found at the third measuring point identified more subsequently successful players than random selection would. This pattern is characterised by above-average, but not necessarily the best, performance on the tests. Developmental paths along structurally stable patterns that occur more often than predicted by chance indicate that the Motor Function subsystem is a viable means of forecasting in the age range of 12-15 years. Above-average, though not necessary outstanding, performance both on fitness and technical tests appears to be particularly promising. These findings underscore the view that a holistic perspective may be profitable in talent selection.